Microbial oil – A plausible alternate resource for food and fuel application. (June 2017) - Bharathiraja, B.; Sridharan, Sridevi; Sowmya, V.; Yuvaraj, D.; Praveenkumar, R.
Graphical abstract: Highlights: Emerging potential feedstock with higher degrees of scope in the near future. Balance the supply-demand curve due to insufficient feedstock availability. It yield green fuels which are the need of the hour due to rapid climatic changes. Demonstrate in depth the caliber of a wide variety of microbes and their yields. Abstract: Microbes have recourse to low-priced substrates like agricultural wastes and industrial efflux. A pragmatic approach towards an emerging field- the exploitation of microbial oils for biodiesel production, pharmaceutical and cosmetic applications, food additives, biopolymer production will be of immense remunerative significance in the near future. Due to high free fatty acid, nutritive content and simpler solvent extraction processes of microbial oils with plant oil, microbial oils can back plant oils in food applications. The purpose of this review is to evaluate the opulence of lipid production in native and standard micro-organisms and also to emphasize the vast array of applications including food and fuel by obtaining maximum yield.